Cable insulation health VI - Wu, Jolene Shi Yan (Nanyang Technological University, 2022)
In Singapore, underground cable such as cross-linked polyethylene cable (XLPE) is being used to transmit electrical power from power plant to consumers. The cable's health (durability and effectiveness), which is determined by its insulation, is crucial for maintaining smooth and consistent power supply delivery. The degradation process is a significant problem in cable insulation. Due to various stresses, the cable insulation deteriorates with time. Hence, cable testing (IR test) is required on a regular basis to detect impurities or damage and ensure that the cable is in excellent working condition. Step Voltage Test was used to test the healthiness of cable insulation among various cable tests such as Spot Reading, Time – Resistance Test etc. Polarisation Depolarisation Current (PDC), Polarisation Index (PI) and Dielectric Absorption Ratio (DAR) was then used to further assess cable health. To do so, 3 cable of different aging state, length and brand was tested on. It was found that the 1987 Cable was the healthiest.